Mitigating fragility in open-ended investment funds: The role of redemption restrictions - Luis Molestina Vivar (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2024)
Using supervisory data of alternative investment funds investing in bonds, I exploit the COVID-19 crisis to examine the effectiveness of redemption restrictions. First, I find that redemption restrictions reduced outflows during the March 2020 market turmoil but did not result in higher outflows in the periods following the crisis episode. Second, I find that funds with higher redemption restrictions engaged less in procyclical cash hoarding during the COVID-19 crisis period, even after controlling for the size of their outflows. Third, I find that redemption restrictions do not have a significant impact on the sensitivity of investor inflows to good performance, but they significantly reduce the sensitivity of outflows to bad performance. These findings suggest that redemption restrictions can mitigate fragility in open-ended investment funds.
Keywords: G11; G15; G23; 330; bond funds; redemption restrictions; notice period; financial fragility